The Importance of Primary Prevention Regarding Orientations Given to Babies´ Caregivers - Anauate, C; Peters Kahhale, E (KnE Life Sciences, 2018)
Caregiver orientation is very important to promote neurodevelopment on babies. Considering that relations are the key for this development of superior mental functions, we believe that all caregivers, teachers and parents should be present and paying attention to the children, providing opportunity for an ideal neurodevelopment and humanization. It is important to orientate caregivers so that they can provide qualitative conditions, which integrate affection, conscience and action to promote development to occur according to the potential of the child. We believe that the individual constitutes himself by means of social contact. This work has the goal to approach the theory which orientates, with specific guidelines and practical work, caregivers aiming a better child neurodevelopment. Bonds are necessary for a better and trustful relation. When you are present in a relation nervous connections are promoted and these lead to a more effective motor, cognitive and affective development of the superior mental functions such as memory, attention, language, psychomotricity and executive functions. It uses didactically the following principles of the Social Historical theory of Luria and Vygotsky: mediation, functional units and zone of proximal development. Interactions between the brain and the formation of mental functions require the maturity of the nervous system as well as an active process that emphasizes relations of two or more human beings. Keywords: neurodevelopment, childhood, relation